2019
DOI: 10.1002/adfm.201904465
|View full text |Cite
|
Sign up to set email alerts
|

Full Energy Spectra of Interface State Densities for n‐ and p‐type MoS2 Field‐Effect Transistors

Abstract: 2D materials are promising to overcome the scaling limit of Si field-effect transistors (FETs). However, the insulator/2D channel interface severely degrades the performance of 2D FETs, and the origin of the degradation remains largely unexplored. Here, the full energy spectra of the interface state densities (D it ) are presented for both n-and p-MoS 2 FETs, based on the comprehensive and systematic studies, i.e., full rage of channel thickness and various gate stack structures with h-BN as well as high-k oxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 65 publications
4
52
1
Order By: Relevance
“…, which is consistent with other published data [4]. By optimizing the interface between MoS 2 channel and gate oxide, D it can be reduced and µ can be improved.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…, which is consistent with other published data [4]. By optimizing the interface between MoS 2 channel and gate oxide, D it can be reduced and µ can be improved.…”
supporting
confidence: 91%
“…That results in a large amount of numerical calculations in previous models [7,8]. On the other hand, according to experimental results [4], Cq increases exponentially with Vgs and thus C it is negligible in the strong-inversion region. In the sub-threshold region, the sub-threshold swing (SS) is dominated by C it and Cox.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…10(b), the defects states for NbMo are formed just below the valence band maximum [71]. However, interestingly, the defect density of NbMo is smaller than that of VS, even in the Nb-doped p-type MoS2 crystal [21,72]. Moreover, it is reported that p-type conduction for the "n-type" monolayer MoS2 FET was not detected, even using the ion gating; instead, the abnormal conductance peak was observed due to the defect states of VS [73].…”
Section: Origin Of Dit In N-type and P-type Mos2 Fetmentioning
confidence: 95%